Is Abū Bakr Muḥammad ibn Zakariyyā Al-Rāzī Plagiarist? (The historical study of Al-Rāzī’s Metaphysical Thought) - Nafisah Nafisah (Ulumuna, 2016)
This paper examines the origins of metaphysical thought of Abū Bakr Muḥammad ibn Zakariyyā al-Rāzī. His metaphysics proposes five eternal principles which include (1) God (al-Bārī Subh\ānah), (2) universal soul (al-nafs al-kulliyah), (3) primeval matter (al-hayūla al-awwālah ), (4) absolute place (al-makan al-mutlaq), and (5) absolute time (al-zamān al-mutlaq). Some people argued that al-Rāzī took these ideas from other thinkers, or any teachings which were being developed at the time. Hence, these five principles are not his thought originally. Where does this doctrine come from? This library research utilizes the main data from al-Rāzī book entitled Rasā’il Falsafiyyah, particularly on the chapter of 'Al-Qudamā al-khamsah', and 'al-‘Ilm al-Ilāhi' and 'sīrah Falsafiyyah'. Other books that related to his thought are also explored to support the data in this research. This study proves that al-Rāzī develops these five concepts himself. He did not plagiarize others when writing his book as well formulating his view of metaphysic. DOI: http://dx.doi.org/10.20414/ujis.v20i2.796